Effect of build orientation on mechanical properties of epoxy resin reinforced coconut fiber - Ahmad Bakhtiar, Mukhtar (2009)
Composite materials and layered structures based on natural plant fibers are increasingly regarded as an alternative to glass fiber reinforced parts. One of their major fields of application can be found in structural components for the automotive industry. Product examples are door trim panels or instrument panels. For such applications utmost impact strength is required in order to implement a maximum of passenger safety by a good crash behavior. This study is carried out to investigate the mechanical properties of epoxy resin reinforced coconut fiber and describes the effect of build orientation or arrangement parameters based on tensile testing of the process conditions on this important composite characteristic. From the experiment, it was found that the addition of the coconut fiber into polymer matrix had increased the tensile strength of the composite. But, the tensile strains of the composites are decreasing when the fiber is added into the polymer matrix. However, the modulus of elasticity of the reinforced epoxy is increased compared to unreinforced epoxy.